How does artificial intelligence impact digital healthcare initiatives? A review of AI applications in dental healthcare - Syed Sarosh Mahdi; Gopi Battineni; Mariam Khawaja; Raheel Allana; Maria K Siddiqui; Daniyal Agha (International Journal of Information Management Data Insights, 2023)
The use of artificial intelligence (AI) technology in dentistry provides information that aids clinical decision-making by interpreting big data quickly. This study aims to systematically review the current role of AI in dentistry where it has a significant impact on clinical dentistry. Document collection was done from 1990 to 2022 based on the main themes of AI-assisted dentistry. This document extraction was done by utilizing PubMed, Embase, CINAHL, and Google Scholar libraries with different Medical Subject Headings (MeSH). This search result revealed different numbers of publications under the search terms AI in dentistry (N=1289), AI role in the diagnosis of dental caries (N=4), AI in dental diagnostic and treatment planning (N=68), AI and dental caries (N=76), the future of dentistry with AI (N=5), and Machine learning in dentistry (N=668). A fast-emerging technology like AI can certainly replace manual dexterity in dentistry. To reduce errors and oversight, these technologies must also be used with caution and under human supervision. The fastest and most accurate diagnosis of oral diseases leads to better outcomes for patients.